Heterogeneous Ownership Structure and Audit Report Timeliness of Listed Consumer Goods Firms in Nigeria - Olugbenga, Folorunso Paul; Ekwe, Michael Chidiebele; Nwobu, Obiamaka Adaeze (International Journal of Economics and Financial Issues, 2025)
The study investigated how diverse ownership structures influence the timeliness of audit report publication among listed consumer goods companies in Nigeria. It adopts an ex-post-facto design while considering consumer goods companies from 2013-2023. After filtering through all the possibilities, 17 consumer goods firms remained on the Nigeria group exchange (NGX) list as at December 31, 2023. Using the GMM estimations on panel data, the study analyses the influence of ownership concentration, institutional ownership, managerial ownership, and foreign ownership over audit report lag. Results show that ownership concentration and managerial ownership significantly delay the audit reporting process, while foreign ownership enhances timeliness. Institutional ownership shows no significant effect. These results illustrate how ownership configuration affects the efficiency of financial performance. The research therefore recommends the enforcement of stronger regulatory oversight, promotion of foreign ownership, and better corporate governance practices to fast-track audit timeliness and transparency in the Nigerian capital market.